ANALISIS PENGARUH PAJAK EKSPOR TERHADAP KEUNGGULAN DAYA SAING CPO DI INDONESIA - Nurcahyo, Rianto (Lembaga Penerbitan Unversitas Esa Unggul, 2017)
The agricultural sector is one of the economic sources of Indonesian society, especially Crude Palm Oil (CPO). Indonesia is the largest producer of CPO in the world supported by the land area in the country. According to some parties, Indonesian CPOâ€™s export levy policy is still considered ineffective. The government raised export levies as one of the government's policy instruments in reducing the rise in cooking oil prices and government programs in subsidizing bio-diesel. This study aims to identify the existing problems ranging from aspects of CPO production and exports, factors affecting the area, productivity, and export of CPO and also evaluating the influence of export taxes and levies toward sales decisions. Data processing is done qualitatively. The amount of data obtained from the primary data was acquired from interviews with respondents residing in the CPO industry in Indonesia.Â Keyword : cpo, export tax, indonesia